2002
DOI: 10.1074/jbc.m108306200
|View full text |Cite
|
Sign up to set email alerts
|

RAD51C Interacts with RAD51B and Is Central to a Larger Protein Complex in Vivo Exclusive of RAD51

Abstract: RAD51B and RAD51C are two of five known paralogs of the human RAD51 protein that are thought to function in both homologous recombination and DNA double-strand break repair. This work describes the in vitro and in vivo identification of the RAD51B/RAD51C heterocomplex. The RAD51B/RAD51C heterocomplex was isolated and purified by immunoaffinity chromatography from insect cells co-expressing the recombinant proteins. Moreover, co-immunoprecipitation of the RAD51B and RAD51C proteins from HeLa, MCF10A, and MCF7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 25 publications
(43 reference statements)
4
62
0
Order By: Relevance
“…This is the first in vitro evidence for Rad51⅐Rad51C⅐Rad51B complex formation. However, in the course of our study, it was reported that overexpressed His 6 -tagged Rad51C did not pull down Rad51 in human cells (43,44). Because we observed that the interaction between Rad51C and Rad51 is weak, only ϳ5-10% of the overexpressed Rad51 was pulled down by the Rad51B⅐Rad51C complex in insect cell extracts as well as by purified complex of Rad51B and Rad51C proteins, the failure to detect the Rad51C-Rad51 interaction in human cells (43,44) is likely due to the weak interaction between the Rad51B⅐Rad51C complex and Rad51.…”
Section: Discussionmentioning
confidence: 71%
“…This is the first in vitro evidence for Rad51⅐Rad51C⅐Rad51B complex formation. However, in the course of our study, it was reported that overexpressed His 6 -tagged Rad51C did not pull down Rad51 in human cells (43,44). Because we observed that the interaction between Rad51C and Rad51 is weak, only ϳ5-10% of the overexpressed Rad51 was pulled down by the Rad51B⅐Rad51C complex in insect cell extracts as well as by purified complex of Rad51B and Rad51C proteins, the failure to detect the Rad51C-Rad51 interaction in human cells (43,44) is likely due to the weak interaction between the Rad51B⅐Rad51C complex and Rad51.…”
Section: Discussionmentioning
confidence: 71%
“…In the absence of EME1, chromosomal aberrations occurred and led to genomic instability (Abraham et al, 2003). The gene RAD51L1 (fc: 11.395, DON2.5) functions in homologous recombination and DNA double-strand break repair (Miller et al, 2002). CHAF1B (fc: 1 1.435, DON5) is part of the complex CAF-1 and the only subunit available on the Chicken Genome Array.…”
Section: Dna Repairmentioning
confidence: 99%
“…a heterodimer of Rad51C and XRCC3 and a larger complex comprising Rad51B, Rad51C, Rad51D, and XRCC2 (18, 20 -22). The transient existence of Rad51B-Rad51C and Rad51D-XRCC3 heterodimers also has been suggested (21,22,56). It seems probable that the various paralog complexes form dynamically during the process of HR (21).…”
Section: Rad51c Dynamically Influences the Protein Levels Of Other Rad51mentioning
confidence: 99%